Republic of Slovenia : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Slovenia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that economic performance of Slovenia strengthened in 2006, supported by a recovery in investment and continued growth spillovers from the European Union. Declining real interest rates in the run-up to euro adoption on January 1, 2007 helped sustain credit growth and domestic demand. The strong economy boosted job creation, while unemployment declined and capacity utilization reached record high levels. Growth is projected to slow down slightly in 2007-08, as the investment boom decelerates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet